The Crossing Effect of Dragon Fruit Plant Caltivars [Hylocereus Sp.] on Yield - Subandi, Muhammad; Mustari, Eri; Setian, Arie (International Journal of Engineering and Technology, 2018)
Type of dragon fruit that is cultivated commercially is the red dragon fruit. There is no optimal production, because the flower of plant is incompatible. One way of improving production [fruiting] of dragon fruit is through manual crossing. This research aim was to study the crossing suitabilityof the red dragon fruit on fruiting. The research was conducted in dragon fruit plantation, West Java. Experimental design used was Randomized Block Design with four treatments and six replications. Treatments were: Natural Pollination [control];Crossing in one flower;Crossing between flowers; Crossing between varieties. Dimension of fruit measured were:diameter, length, fresh weight, and sugar content of fruit. Analysis of variance was applied with Duncan test at 5% significance level. Preparation of flower pollination was done by selecting the probable flower to bloom at night to come. The blooming flower can be predicted in the afternoon and the crossing was done at midnight.The result showed that the crossing between varieties was the best [improved fruiting]production.Â  This report was suplemented with literature study on betalain showing that betalain is great beneficial for human health, and may be the next subject to study once the bulk production of fruit is done.